On the Role of Vocal Idioms in Singing - Stark, James (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
The identification of particular vocal techniques in singing, which combine to form distinctive vocal idioms, is important for an understanding of both "classical" and "vernacular" musical styles. The modern critical literature on song is based largely on the limited concept of a "word-tone relationship," with musico-poetic synthesis as its ideal. Performance practices are as important to song criticism as is the study of written scores. The elements of voice quality and vocal articulation, with specific reference to the physiology and acoustics of the human voice, provide the analytical tools for defining vocal idioms and their role in the value and success of a song. The description of such idioms requires a rapprochement between vocal history, pedagogy, and science. Using the bel canto paradigm as a reference point, this article discusses a variety of vocal idioms. Gluck's aria, "Che farò senza Euridice" is used to illustrate how an understanding of vocal idioms can alter our judgment of a piece which has sometimes been condemned for its poor word-tone relationship.